Affixation Category of Palembang Malay Language Reviewed From Perspective of Morphological Typology - Husni Thamrin Thamrin (JOMANTARA, 2021)
This research is related to affixation category of Palembang Malay language, which is a regional part of the Sumatra region exactly South Sumatra. In particular, this study uses category of affixation in the form of prefixes and suffixes (suffiks) used by Dryer's (2013) in researching the Nualu language in Seram island which belongs to the Polynesian Malay ethnic. This research reveals that on Palembang Malay language affixation, the first affixation category was the form of 6 (six) categories of prefixes (awalan) in Palembang Malay language, among others; N-, di-, peN-, be-, te-, and se-.Second, there are found 5 (five) types of suffixes (akhiran) in Palembang Malay language, such as; -ke, -la, -an, -nyo, and –i. The third is found 3 (three) simulfix (awalan-akhiran) which is the type of bound form of the prefix one with another prefix, such as: ke-.. . -an, pe-. . . -an, and be-. -an. Finally, there were found 3 (three) main categories of morphophonemic process prefixes in Palembang Malay language, such as; a) there are four types of prefixesN-in Malay language Palembang has many allomorphs: m, n, ny, ng. b) there are six types of prefixespeN- connected with words, so the prefix will change to: pem-, pen-, peny-, peng-, pel-, orpe-. c)there are four prefixesbe- that has allomorphs bel-, ber, and be- .The Grand theory approach used in this study has been stated by Velupillai (2012) and Lieber (2009).